Food and nutrient intake among non-pregnant, non-lactating women of reproductive age of Mbeya in Tanzania: A repeated 24-hour dietary recall. - Nyamizi J Ngassa; Ray M Masumo; Adam Hancy; Esther J Kabula; Erick Killel; Jackline Nusurupia; Adeline Munuo; Hoyce Mshida; Rose Mpembeni; Elizabeth Lyimo; Rose V Msaki; Theresia Jumbe; et al. (PLOS Global Public Health)
Micronutrient deficiencies can hurt the health of women of reproductive age (WRA), their pregnancy outcomes, and the growth and development of their offspring in sub-Saharan African countries. The present study aimed to estimate the dietary intake of non-pregnant and non-lactating (NPNL) WRA, residing in seven districts of the Mbeya region in Tanzania using a 24-hour dietary recall. A cross sectional study was conducted among 500 NPNL WRA. A two-stage sampling method was used, three enumeration areas (EAs) were chosen for each district using the probability proportional to size and, 24 eligible households were randomly selected from each chosen EA.The SAS macros (version 9.4) were used to analyse the quantities consumed and explore the usual intakes of three fortified food vehicles. The median intake of oil, wheat flour, and calories was 36.47g, 110.53g, and 2,169.9 kcal, respectively. The median protein intake was 63.5g, higher than the recommended value of 56.0g. Among the micronutrients, zinc had the highest prevalence of inadequate intake (91.2%), followed by iron (82.2%), and vitamin B12 (80.0%). Vitamin E had the highest nutrient gap (50.7%), while the nutrient gap in Q1 was relatively low (9.8%). There was a moderate prevalence of inadequate intake of vitamin C (46.5%) and riboflavin (54.8%), with a nutrient gap in Q1 (42%). Inadequate intake of vitamin A, thiamine, niacin, vitamin B6, and folate was moderate, ranging from 32.6% to 44.4%, with a nutrient gap at Q1 ranging from 16.2% to 34%. Our study has revealed a prevalent inadequate intake of micronutrients among NPNL WRA. Furthermore, our findings suggest that fortifying oil represents a promising intervention. However, fortified wheat flour had limited reach among NPNL WRA in the Mbeya region of Tanzania.